ROASTED CASHEW NUT KERNEL (ANACARDIUM OCCIDENTALE L.) SUPPLEMENTATION IMPROVES HEPATIC AND RENAL STATUS BUT NOT LIPID PROFILE IN RATS - Famurewa, Ademola C; Abi, Innocent; U Eru, Emmanuel (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Although studies suggest that nut consumption is associated with a variety of beneficial health outcomes, however, there is a dearth of data in the literature to document this effect for roasted cashew nut kernel (RCNK). Our objective was to determine whether dietary consumption of RCNK could improve lipid profile, hepatic and renal status in rats. Methods: A total of 24 rats were randomly divided into four groups: A control and three experimental groups fed with roasted cashew nutsupplemented diet at different concentrations for 28 consecutive days. After the experimental period, rats were anesthetized with ether and retroorbital blood samples were withdrawn. Serum samples were obtained to analyze lipid profile, markers of oxidative stress, hepatic and renal status using standard methods. Results: The supplemented diet significantly decreased the liver function parameters in rats. All the concentrations of RCNK in diets significantly reduced serum creatinine and urea levels. However, total cholesterol and low-density lipoprotein-cholesterol (LDL-C) were significantly increased, whereas oxidative stress markers and malondialdehyde were improved by the supplemented diet, although insignificantly, as compared with the control. Conclusions: These results suggest that RCNK may have beneficial health effects on the liver and kidney status although marked improvement was not demonstrated in oxidative stress markers. However, the significant increase in serum total and LDL-C indicates the need for further studies. Keywords: Roasted cashew nut, Anacardium occidentale, Lipid profile, Liver enzymes, Oxidative stress.